PENGARUH BUDAYA ORGANISASI DAN WORK LIFE BALANCE TERHADAP EMPLOYEE ENGAGEMENT DI PT ARTAJASA PEMBAYARAN ELEKTRONIS - Maria Gabrilla Yubellia (2022)
Companies with high employee engagement are able to achieve success from the creativity of their employees. The success of employee engagement in a company, namely PT Artajasa Pembayaran Elektronis can be seen from the organizational culture and work life balance that has been fulfilled and running well. Sometimes an organizational culture that has a strong sense of kinship such as helping each other can cause employees' tendencies to support colleagues in doing their work so that employee commitment and contribution is reduced. In addition, the working hours of employees during the pandemic exceeded the standard normal working hours of 8 working hours/day due to the leader assumption that when employees work from home, employees can work anytime. This research is a quantitative research that aims to determine the influence of organizational culture and work life balance on employee engagement in PT Artajasa Pembayaran Elektronis. This research has a population of 300 employee respondents with the sample selection using slovin formula calculation and non-probability sampling technique (purposive sampling). Therefore, the research sample used is 75 employee respondents. Data measurement in this research is using questionnaires and likert scale. The analysis technique used is inferential analysis method and hypothesis testing (partial t testing, simultan f testing and R-Square) supported by SmartPLS 3.0 program.